Theory-related translation research. Some thoughts on methodology - Gerzymisch-Arbogast, Heidrun (HERMES - Journal of Language and Communication in Business, 2001)
The article illustrates some methodological principles for translation research and for writing theory-related research papers. A number of postulates are formulated with respect to basic structural dimensions of organizing research papers (working hypothesis, ‘state of the art’ in research, solution proposal and validity test). Examples for norm-compliant behavior are given. Since the problem of writing the ‘state of the art’ of research seems to be one of the major problems facing young scholars, particular emphasis is given to this aspect.